An Evaluation of Personalised Supports to Individuals with disabilities and Mental Health Difficulties - Garcia Iriarte, Edurne (Genio Trust, 2014)
This report gives an overview of the findings from an evaluation of 23 projects that Genio grant-aided in 2010 and 2011 to facilitate personalised housing and support arrangements for persons with intellectual disabilities, mental health difficulties and physical disabilities. This report on the findings has been written primarily for service providers and commissioners. The more technical aspects of the research that was undertaken are available in a series of technical reports which are available on request from Prof. McConkey. Our aim is to make the findings accessible and to identify the implications for future decision-making with regard to transforming and extending current accommodation and support arrangements in Ireland for persons with disabilities and enduring mental health difficulties.